Description of the female of Smerkata zolotuhini (Lepidoptera: Endromidae) - Saldaitis, Aidas; Volynkin, Anton V. (Zootaxa, 2018)
Smerkata Zolotuhin, 2007 has been described as a subgenus of Mustilia Walker, 1865 (Zolotuhin 2007), and recently upgraded to the genus level by Wang et al. (2015). Smerkata zolotuhini (Saldaitis & Ivinskis, 2015) was recently described from western part of Sichuan province of China based on male specimens, as females were unknown at the time (Saldaitis et al. 2015). Recent collecting has provided additional specimens, including females described below.